2021
DOI: 10.1111/1365-2435.13850
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tolerance of early development predicts the realized thermal niche in marine ectotherms

Abstract: Predictions of ectotherms' responses to global warming depend on the relationship between environmental temperature and organismal performance. To date, most predictions of thermal responses are generated from experimentally derived measures of thermal tolerances of adults or estimates of thermal niches derived from geographic distributions of adults. It is unknown how measures derived from these different approaches compare, or, as thermal performance of ectotherms varies through ontogeny, how they compare ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 69 publications
(98 reference statements)
3
25
0
Order By: Relevance
“…Such an interpretation is of course speculative at this point. Our results do, however, add to mounting evidence pointing to embryogenesis as the most critical of early life stages in aquatic ectotherms, not only for the emergence of thermal sensitivity ( Dahlke et al, 2020 ; Rebolledo et al, 2020 ; Collin et al, 2021 ), but also of thermal carryover effects. Although, our results suggest that fertilization matters less in this regard, the possibility remains that the environment at gametogenesis is more influential than the environment at fertilization, emphasising the need to better understand transgenerational effects on thermal performance.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Such an interpretation is of course speculative at this point. Our results do, however, add to mounting evidence pointing to embryogenesis as the most critical of early life stages in aquatic ectotherms, not only for the emergence of thermal sensitivity ( Dahlke et al, 2020 ; Rebolledo et al, 2020 ; Collin et al, 2021 ), but also of thermal carryover effects. Although, our results suggest that fertilization matters less in this regard, the possibility remains that the environment at gametogenesis is more influential than the environment at fertilization, emphasising the need to better understand transgenerational effects on thermal performance.…”
Section: Discussionsupporting
confidence: 64%
“…Nevertheless, most studies to date measure thermal performance and sensitivity at single life stages ( Byrne et al, 2020 ) and predominantly in adults ( Truebano et al, 2018 ; Pandori and Sorte, 2019 ). This is problematic in light of emerging evidence that reproductive stages and embryos tend to be more thermally sensitive and may better predict the vulnerability of ectotherms to climate warming ( Dahlke et al, 2020 ; Rebolledo et al, 2020 ; Collin et al, 2021 ; Van Heerwaarden and Sgrò, 2021 ). Moreover, thermal performance at these critical stages is often incompletely characterized due to well-known challenges in gathering sufficient data, so that information about ontogenetic shifts in thermal limits and thermal optima, in particular, currently remains too limited to identify any general patterns ( Kingsolver and Buckley, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cool and warm temperature limits for 50% echinopluteus larvae (EL 50 ) were used to determine larval cool and warm tolerance (CT, WT) (Collin et al, 2021; Deutsch et al, 2008). Cool tolerance (CT) was determined as the difference between the cool EL 50 and the mean ambient local SST during winter (18.6°C, Wolfe et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In diverse marine invertebrates, embryonic or larval stages commonly exhibit greater sensitivity to environmental stressors than adults (Przeslawski et al, 2015). Salinity or temperature gradients can limit adult distributions by impeding supply-side processes when conditions exceed embryonic or larval tolerance (Mann and Harding, 2003;Sanford et al, 2006;Collin et al, 2021). Here we found that embryos of both species were notably more vulnerable to prolonged immersion in low salinity than larvae or adults.…”
Section: Physiological Thresholds Across Life Stagesmentioning
confidence: 57%